Influence of Decadal Variability of Global Oceans on South Asian Monsoon and ENSO-Monsoon Relation ... - Krishnamurthy, Lakshmi (George Mason University, 2012)
This study has investigated the influence of the decadal variability associated with global oceans on South Asian monsoon and El Niño-Southern Oscillation (ENSO)- monsoon relation. The results are based on observational analysis using long records of monsoon rainfall and circulation and coupled general circulation model experiments using the National Center for Atmospheric Research (NCAR) Community Climate System Model (CCSM) version 4 model. The multi-channel singular spectrum analysis (MSSA) of the observed rainfall over India yields three decadal modes. The first mode (52 year period) is associated with the Atlantic Multidecadal Oscillation (AMO), the second one (21 year) with the Pacific Decadal Oscillation (PDO) and the third mode (13 year) with the Atlantic tripole. The existence of these decadal modes in the monsoon was also found in the control simulation of NCAR CCSM4. The regionally de-coupled model experiments performed to isolate the influence of North Pacific and North Atlantic also substantiate ...